Synergistic combinations of novel polymyxins and rifampicin with improved eradication of colistin-resistant Pseudomonas aeruginosa biofilms - Johan Storm Jørgensen; Anne Sofie Laulund Siebert; Oana Ciofu; Niels Høiby; Claus Moser; Henrik Franzyk (Biofilm)
Background: Increased prevalence of antimicrobial resistance coupled with a lack of new antibiotics against Gram-negative bacteria emphasize the imperative for novel therapeutic strategies. Colistin-resistant Pseudomonas aeruginosa constitutes a challenge, where conventional treatment options lack efficacy, in particular for biofilm-associated infections. Previously, synergy of colistin with other antibiotics was explored as an avenue for the treatment of colistin-resistant infections, and recently we reported our efforts towards colistin analogs capable of combating planktonic colistin-resistant strains. Aims: The aim of the present study was to investigate whether analogs of polymyxin B with improved potency in wild-type and moderate resistant Gram-negative pathogens would retain similarly increased activity in highly colistin-resistant clinical P. aeruginosa isolates (in planktonic and biofilm growth) when applied alone and in combination with rifampicin. Materials and methods: In this in vitro study, we tested three analogs of polymyxin B prepared by solid-phase peptide synthesis. Antimicrobial susceptibility testing was performed by measurement of minimum inhibitory concentrations via the broth microdilution method. Interactions between two antimicrobials was quantified in a checkerboard broth microdilution assay by calculating the fractional inhibitory concentration index for each combination. For testing of antibiofilm activity a previously described model with alginate beads encapsulating a biofilm culture was applied. The minimum biofilm eradication concentrations (MBECs) were evaluated, and the fractional biofilm eradication concentration indices were calculated. Three recently identified colistin analogs (CEP932, CEP936 and CEP938) were tested against three isogenic pairs of colistin-susceptible and colistin-resistant P. aeruginosa clinical isolates as well as the reference strain PAO1. Results: For bacteria in planktonic growth CEP938 retained almost full potency in all three resistant isolates, while exhibiting similar activity as colistin in susceptible isolates. Against biofilms CEP938 was slightly more potent against PAO1 as compared to colistin, while also retaining activity against a biofilm of the colistin-resistant strain 41,782/98. Next, synergy between CEP938 and the antibiotic rifampicin was explored. Interestingly, CEP938 did not exhibit synergy with rifampicin in planktonic cultures. Importantly, for colistin-resistant biofilms the CEP938-rifampicin combination demonstrated activity superior to that found for the colistin-rifampicin combination. Conclusions: The present study showed in vitro efficacy of CEP938 against both colistin-susceptible and colistin-resistant P. aeruginosa biofilms as well as an ability of CEP938 to synergize with rifampicin in biofilm eradication.